
Explanation:
The triangle is right angled.
The formula for area of the triangle:

base = 3
height = 4
substitute the values:
Answer:
Step-by-step explanation:
J we be w e e e e d. D
We will find the inverse of the given functions:
y = x + 2 / x-2
(x-2) y = x + 2
-2y + xy = x + 2
-2y + xy = x + 2
x (y - 1) = 2 + 2y
x (y - 1) = 2 (y + 1)
x = 2 (y + 1) / (y - 1)
f (x) ^ - 1 = 2 (x + 1) / (x - 1)
The inverse is different.
f (x) = x + 1 / x-1
y = x + 1 / x-1
(x-1) y = x + 1
-y + xy = x + 1
x (y - 1) = 1 + y
x (y - 1) = (y + 1)
x = (y + 1) / (y - 1)
f (x) ^ - 1 = (x + 1) / (x - 1)
The inverse is the same.
Answer:
f (x) = x + 1 / x-1
f (x) ^ - 1 = (x + 1) / (x - 1)
f (x) = f (x) ^ - 1